Seismic Behavior Analysis of Composite Buildings with Respect to RCC Buildings - Dahal, Sunita; Suwal, Rajan (Journal of the Institute of Engineering, 2019)
Steel concrete composite construction has gained wide acceptance worldwide as an alternative to pure steel and pure concrete construction. The use of steel in construction industry is very low in Nepal compared to many developing countries. There is a great potential for increasing the volume of steel in construction, especially in the current development needs. Not using steel as an alternative construction material and not using it where it is economical is a heavy loss for the country. Use of composite material is of particular interest, due to its significant potential in improving the overall performance through rather modest changes in manufacturing and constructional technologies. Steel concrete composite construction means the concrete slab is connected to the composite beam with the help of shear connectors so that they act as a single unit. In the present work, steel concrete composite (both full and half composite) with RCC options are considered for comparative study of seismic behavior of 10 multistoried commercial buildings (4-storied, 5-storied, 6-storied, 7-storied, 8-storied, 9-storied, 10-storied, 12-storied, 16-storied and 20-storied which is situated in earthquake zone V and for earthquake loading, the provisions of IS:1893 (Part1)-2002 is considered. For modeling of composite and RCC structures, SAP2000 software is used. Steel-concrete composite construction system is an efficient, economical and innovative method for seismic resistance of multi storied buildings. Equivalent static method of seismic analysis is used in the analysis of models. Comparison of parameters like time period, axial force, shear force, bending moment, deflection, storey drifts, base shear, storey stiffness is done for full composite (beam-column both composite), half composite (column composite) and RCC structures. The results are compared and found that composite structure is better in several aspects.